Town & country : a novel - Schaefer, Brian (Atria Books, 2025)
"The trendy rural town of Griffin has become a popular destination for weekenders and the city's second homeowners, but now a congressional race in this swing district is highlighting tensions between life-long residents and new arrivals. The campaign pits local pub owner and town supervisor Chip Riley against the wealthy young carpetbagger Paul Banks, challenging the social and political loyalties of their families and friends with lasting repercussions. Diane Riley, Chip's wife, is a religiously devout real estate agent who feels conflicted about selling second homes--including to Paul and his much older husband, Stan. Their elder son, Joe, is grieving the recent overdose death of his best friend and spiraling into drugs himself, while their younger son, Will, is a newly out college student seduced by the decadent lifestyle of Paul's circle. Meanwhile, Stan Banks uses the race to give purpose to the pain of losing a loved one to AIDS, even as he begins to doubt Paul's readiness for office. And within their growing fraternity of city transplants, Eric Larimer finds unexpected connection with a local farmer that opens his eyes to the region's complexity as Leon Rogers, still reeling from a divorce, becomes increasingly desperate to infiltrate the Banks's exclusive crew"--